2022
DOI: 10.3390/microorganisms10040771
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Growth-Promoting Effect by Cell Components of Purple Non-Sulfur Photosynthetic Bacteria

Abstract: Rhodobacter sphaeroides, a purple non-sulfur photosynthetic bacterium (PNSB), was disrupted by sonication and fractionated by centrifugation into the supernatant and pellet. The effects of the supernatant and pellet on plant growth were examined using Brassica rapa var. perviridis (komatsuna) in the pot experiments. Both fractions showed growth-promoting effects: the supernatant at high concentrations (1 × 107 to 4 × 107 cfu-equivalent mL−1) and the pellet at a low concentration of 2 × 103 cfu-equivalent mL−1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Members of the genus Rhizobium are well-known as a typical symbiosis of leguminous plants, as well as the other plants [ 25 ]. Several species of Novosphingobium promoted plant growth by the production of indole-3-acetic acid (IAA) [ 26 , 27 , 28 ]; while members of Rhodobacter were recognized as plant growth-promoting bacteria [ 29 , 30 ]. Although many potential DAB have been successfully inocculated to duckweeds through culture-dependent [ 7 , 8 , 16 ] and culture-independent methods [ 12 , 16 ], associations occurred for a short period and then vanished [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Members of the genus Rhizobium are well-known as a typical symbiosis of leguminous plants, as well as the other plants [ 25 ]. Several species of Novosphingobium promoted plant growth by the production of indole-3-acetic acid (IAA) [ 26 , 27 , 28 ]; while members of Rhodobacter were recognized as plant growth-promoting bacteria [ 29 , 30 ]. Although many potential DAB have been successfully inocculated to duckweeds through culture-dependent [ 7 , 8 , 16 ] and culture-independent methods [ 12 , 16 ], associations occurred for a short period and then vanished [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The receptor for LPS in plants, named lipooligosaccharide-specific reduced elicitation (LORE), has also been identified [ 21 ]. In our two previous studies [ 18 , 19 ], we proposed that LPS acts as one of the active principles of plant growth-promoting effects of PNSB. In the first study [ 18 ], we disrupted the PNSB cells by sonication in water, and fractionated the cell lysate by centrifugation into the supernatant and pellet, and examined their effects on the growth of Brassica rapa var.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these aforementioned mechanisms, we recently proposed lipopolysaccharide (LPS), a component of the Gram-negative bacterial cell wall, as a new active ingredient in PNSB [ 18 , 19 ]. Hayashi et al [ 18 ] reported the growth-promoting effect of lipopolysaccharide (LPS) from PNSB in plants for the first time, and the effective concentration of LPS from Rhodobacter sphaeroides NBRC 12203 T was 10 pg/mL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hayashi et al [ 16 ] reported the growth-promoting effect of lipopolysaccharide (LPS) from PNSB in plants for the first time, and the effective concentration of LPS from Rhodobacter sphaeroides was 10 pg/mL. In mammals, LPS acts as an endotoxin through the Toll-like receptor 4 (TLR4) signaling pathway at a concentration of pg/mL to ng/mL, causing inflammatory responses.…”
mentioning
confidence: 99%